A Mobility-Aware File System - file availability in a mobile-aware, context aware environment - O'Flaherty, Owen (Trinity College Dublin. Department of Computer Science, 2005)
The rapid growth in number of portable electronic devices with wireless networking capabilities in recent times has thrown up many new computing problems and opportunities. Such devices typically lack the processing power common to more familiar desktop and laptop computers. They are also constrained by their limited power supply. Given the scenario of an urban environment in which a large number of people using such devices constantly move about with a need to share information, it is clear that existing network topologies are inherently unsuited to supporting the sort of applications that they might need. This dissertation project addresses the changing role of that most integral part of computer systems in this new environment - the file system. A distributed file system called Stirling is presented that takes advantage of both the ad hoc nature of the network environment and the structure provided by the WAND (Wireless Ad-hoc Network for Dublin.) This filesystem offers a set of features suited for ad-hoc networking. These features, such as virtual file placement and latency minimisation, may be set and adjusted by users at a finegrained level. It is envisaged that such a system may be put in place on a backbone network such as the WAND in order that users and their devices can be guaranteed ?reachability? to other devices from one end of the network to the other. Usability scenarios are presented and analysed, and test cases documented.
Keywords: Computer Science